2022
DOI: 10.1111/rssa.12955
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Reproduction Numbers in Real Time: Conceptual and Statistical Challenges

Abstract: The reproduction number R has been a central metric of the COVID-19 pandemic response, published weekly by the UK government and regularly reported in the media. Here, we provide a formal definition and discuss the advantages and most common misconceptions around this quantity. We consider the intuition behind different formulations of R, the complexities in its estimation (including the unavoidable lags involved), and its value compared to other indicators (e.g. the growth rate) that can be directly observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…However, their relative merits and demerits have been increasingly debated (see Pellis, Birrell, et al (2021) and Jewell and Lewnard (2021) of this issue for example). Recent work has suggested that the benefits of inferring truer̂t might have been underappreciated, and that this quantity may be particularly useful because of its apparent independence from modelling assumptions and its explicit consideration of the epidemic speed (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their relative merits and demerits have been increasingly debated (see Pellis, Birrell, et al (2021) and Jewell and Lewnard (2021) of this issue for example). Recent work has suggested that the benefits of inferring truer̂t might have been underappreciated, and that this quantity may be particularly useful because of its apparent independence from modelling assumptions and its explicit consideration of the epidemic speed (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the instantaneous epidemic growth rate, rt, defined as the rate of change of the log‐transformed case incidence, has been proposed as a more informative and understandable measure of transmission dynamics (Pellis, Birrell, et al, 2021). Growth rates may be estimated directly from the gradient of the log‐transformed observed incidence curve, have a natural temporal interpretation as the speed of case accumulation and still encode key dynamics, for example, the signs of rt and Rt1 signify similar transmission trends.…”
Section: Introductionmentioning
confidence: 99%
“…We defined the epidemic growth phase of a VOC as the period for which the exponential increase of its weekly reported proportion (%) is a constant during at least 4 weeks in the BGS, which was calculated using a linear regression curve. [42][43][44] The slope value a of the linear regression curve (equation format y = ax + b) within that time window represents the relationship between the detection levels (%) of each VOC in relation with time, and thus provides a measure of how quickly a VOC is growing. The R 2 value was used as a measure of the quality of the linear regression curve for the used dataset.…”
Section: Methodsmentioning
confidence: 99%
“…In the specific context of a pandemic, quantifying transmission dynamics, for example by estimating headline summaries such as the effective reproduction number R t (see Pellis et al, 2022) was of key interest to public health officials. At some point, such summaries were discussed daily.…”
Section: Communicationmentioning
confidence: 99%